2012
DOI: 10.1103/physrevb.85.224509
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of superconducting pairing state in a staggered field

Abstract: In order to investigate the symmetry of a superconducting (SC) pairing state in a staggered field, we solve the linearizedÉliashberg's equation based on the random phase approximation and the fluctuation exchange approximation in the Hubbard model under a staggered field. We show that an odd-frequency spin-triplet (equal-spin) s-wave pairing state can be realized in the system. It is caused by the fact that the staggered field suppresses the in-plane spin susceptibility and enhances the charge susceptibility. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…( 6), whose mean value is given in terms of the Keldysh Green functions as (26) Integrating the expression, and noticing that the contribution outside the gap vanishes, we obtain the expression in Eq. (7) Expression for current noise in the imaginary-time formalism…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 6), whose mean value is given in terms of the Keldysh Green functions as (26) Integrating the expression, and noticing that the contribution outside the gap vanishes, we obtain the expression in Eq. (7) Expression for current noise in the imaginary-time formalism…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that electron-electron interactions mediated by phonons cannot stabilize an odd-ω gap by itself [5]. In contrast, other mechanisms, such as spin, charge, or current fluctuations, may be favorable [6][7][8]. Disordered systems [9,10], heavy fermion compounds [11][12][13][14][15], topological materials [16][17][18], and multiband superconductors [19][20][21][22] have been suggested to host odd-ω pairs in the equilibrium situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6. The reason for this involves the stabilization of odd-frequency pairing near the magnetic transition [113,116]. Although we do not exclude the possibility of oddfrequency pairing in this material, odd-frequency pairings are difficult to obtain at least in the Hubbard model with the parameter set used herein, since the tendency towards SDW ordering saturates at low temperatures.…”
Section: Temperature Dependence Of Eigenvaluesmentioning
confidence: 91%
“…The SC states we considered in this study are both the singlet and triplet channels in spin space, in addition to the even-and odd-frequency pairings [108][109][110][111][112][113][114][115][116]. Adopting the notation of the pairing states from previous studies [72,117,118], we label the pairing states by frequency, spin, parity of the gap function, and gap symmetry in wavenumber space, such as even-frequency, spin-singlet, even-parity (ESE), then the gap symmetry is added from the calculation result.…”
Section: B Spin Susceptibility and The Superconducting-gap Functionmentioning
confidence: 99%